GENERATION OF SEMIAUTOMATIC MORPHOMETRIC DATA: PROPOSED NEW BOUNDARIES OF THE WATER DIVIDER AND ALTIMETRY WATERSHED PERICUMA - MARANHAO, BRAZIL - Viegas, Josue Carvalho [UNESP] (2015)
For the geography and related fields, knowledge of the substrate and the land surface (dynamic topography) in certain regions, assist in indicating skills and restrictions for use and occupation of land, but also indicate some form of prevention and control geographic space. This study proposes the use of images in raster format project - TOPODATA / INPE, which can be applied in the study of geomorphological boundaries of watersheds. The objective is to evaluate the generation of preliminary data to aid the study of the natural fragmentation of the watershed's landscape Pericuma, inserted in the Brazilian Amazon. Thus, it can be seen that the results presented here contradict previous studies in the area. Previous to this study showed that the elevations reached the maximum 50 meters. Already the boundaries of the watershed of Pericuma and the drainage network of water bodies semiautomatically generated, have become loyal information previously processed in the laboratory and confirmed in the field.